An appraisal analysis of jacinda ardern's speech in embracing muslim community after the christchurch mosques terrorism attack - Ajeng Kurniasri Pritadewi (Fak. Adab dan Ilmu Budaya Universitas Islam Negeri Sunan Kalijaga, 2021)
wt,1/ yna, c.1